Bidding on a Texan - Dunlop, Barbara (Texas Cattleman's Club: heir apparent., 2021)
Cowboy restaurateur Rafe Cortez-Williams blames the wealthy Edmonds family for swindling him and the folks of Royal, Texas, out of millions. So when Gina Edmonds proposes a fundraiser to recoup the losses, Rafe is skeptical, until the gorgeous, sheltered heiress proposes a cowboy bachelor auction- with Rafe as the main prize. By the time the gavel comes down, he can't say no to their explosive attraction, which sets off a chain reaction of secrets this ranching heir never bargained for!